Objeto y materia de estudio de la lingüística. A propósito de la toponimia y sus métodos - Rubio, Luis Fernando (2017)
The following paper is interested in the theoretical aspect of linguistic work. That is why it points out its importance when dealing with disciplines such as linguistics, which work on objects that are the product of theoretical reflections. For this purpose, we try to distinguish which are the different objects of study used in a field of linguistics such as toponymy. The main objective is to demonstrate how the objects used for linguistic analysis are, in reality, the result of a theoretical and methodological elaboration guidedby the particular interests and objectives of the researcher